Understanding the impact of semantics of discount offer communication on consumer buying behavior - Twinkle Pajiyar, Vedantsing Pardeshi, Mihir Belgaonkar, Preetha Menon (International Journal of Advanced Science and Technology, 2020)
Various companies adopt different schemes to present their discount offerings to the customers. A discount offering is an incentive to the buyer to buy a product. The framing of discounts makes that buying decision quick. This research is intended to examine the impact of the differing semantics for the discount offerings made for various types of products. This research paper focuses on the economic view of the consumer while buying a product. The study was conducted to see whether offers indicated as a percentage off or mentioned as a fixed amount discount has more impact. The eye tracking system was used to analyze the patterns in attention span of the customers and understand what attracts them more. The sample size consisted of respondents from an age group of 20-27 years of genders male and female. The respondents had a prior experience of availing discounts and generally preferred buying products with discounts. Advertisements with relevant details were shown to the subjects and their focus attention to the different parts of an advertisement were noted through eye tracking experiment. Industries covered under the study were hypermarket/grocery, travel, banking and jewelry stores. Metrics like time to reach to an area of interest and time spent on an area of interest were noted. The analysis confirmed that for stores offering items of daily usage like groceries the customers preferred to get a fixed amount discount rather than percentage discount. For products of higher worth, the customers preferred percentage discounts. These results can be used as a reference by the brands to take a decision while presenting different discount offerings to their customers